Validity of pleural lactate dehydrogenase measurements in assessment of pleural effusions - Elisna Syahruddin; Lia G. Partakusuma; Rita Khairani (Faculty of Medicine, Universitas Trisakti, 2012)
Background Pleural effusions are classified into transudates and exudates based on Light’s criteria, but the main disadvantage of Light’s criteria is the misclassification of transudates as exudates in about 20% of cases. The aim of this study was to determine the validity of various biochemical parameters to differentiate pleural exudates and transudates.MethodsAn observational study to evaluate diagnostics tests was conducted at the emergency department of Persahabatan Hospital, Jakarta, from September 2010 until December 2011. In total, 119 patients with pleural effusion were evaluated. Simultaneous pleural effusion and blood samples were examined for lactate dehydrogenase (LDH), total protein, cholesterol and albumin, with the clinical diagnosis as the gold standard. ResultsThere were 104 exudative and 15 transudative pleural effusions. Light’s criteria achieved a higher overall accuracy (sensitivity 97%, specificity 80%, accuracy 95%). The optimum cut off values were pleural fluid to serum ratio of LDH 0.4 (sensitivity 95%, specificity 87%, accuracy 94%) and pleural fluid LDH of 178 IU/L (sensitivity 92%, specificity 87%, accuracy 92%). Pleural fluid cholesterol was 50 mg/dL (sensitivity 89%, specificity 53%, accuracy 85%), pleural fluid to serum cholesterol ratio 0.41 (sensitivity 75%, specificity 53%, accuracy 72%) and serum-effusion albumin gradient 1.3 g/dL (sensitivity 91%, specificity 73%, accuracy 89%). Combination of biochemical tests did not improve sensitivity or accuracy.ConclusionsLight’s criteria remain superior to other biochemical tests, but the new cut off values of LDH pleural fluid to serum ratio of 0.4 and pleural fluid LDH of 178 IU/L appears to yield a slight improvement in diagnostic accuracy.